2012
DOI: 10.2176/nmc.52.591
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Sporadic Cerebellar Hemangioblastoma and Pituitary Null Cell Adenoma: Simultaneous Expression of von Hippel-Lindau Gene Product

Abstract: Coexistence of brain tumors of different pathologies is rare, and the majority of the cases were related to genetic disorders or secondary tumors occurring after radiotherapy. A 73-year-old man was introduced to the outpatient department suffering from severe nausea and vertigo. Magnetic resonance imaging showed a cystic tumor in the left cerebellar hemisphere and another lesion in the sella turcica. There was no evident family history of von Hippel-Lindau (VHL) disease, and the systemic investigation failed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In the past reports, a 59-year-old woman showed de novo progression of bilateral MMD within a 5-year interval and a 46-year-old woman developed unilateral MMD between 2004 and 2009 [8,9]. Albeit not adult cases, Amlie-Lefond et al [10] reported a 3-month-old patient with MMD and reviewed other 8 cases of early infancy before the age of 1 year, suggesting that MMD can develop very rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…In the past reports, a 59-year-old woman showed de novo progression of bilateral MMD within a 5-year interval and a 46-year-old woman developed unilateral MMD between 2004 and 2009 [8,9]. Albeit not adult cases, Amlie-Lefond et al [10] reported a 3-month-old patient with MMD and reviewed other 8 cases of early infancy before the age of 1 year, suggesting that MMD can develop very rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…She was tested for a paraganglioma panel due to her GIST and acromegaly because SDH genes can cause both GIST and pituitary adenomas [20][21][22][23], and because VHL can be associated with renal cell carcinoma and CNS lesions [24] and rarely with pituitary adenoma [25,26]. She was tested for AIP and MEN1, although her presentation was not suggestive for either of these genes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of pVHL in pituitary adenomas is not well characterized (15,30,31). In a previous study, examination of pituitary adenomas (nonfunctioning, growth hormone-producing, adrenocorticotropic hormone-producing, and prolactinproducing adenomas) using VHL40 (epitope was 54-213 of pVHL) found negative staining in 18 of 21 adenomas, but strong staining in coexisting normal pituitary cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…unaware of the clinical information. The whole procedure of pVHL staining was described in our previous paper (15). Diagnostic criteria of staining for VEGF, HIF1-α, and pVHL were defined as 3þ if more than half of the cells showed strong to moderate staining, as 2þ if more than half of the cells showed mild to weak staining, as 1þ if less than half of the cells showed mild to weak staining, and as 0 if no cells showed staining.…”
Section: Methodsmentioning
confidence: 99%